Literacy Minimum Assessment Competency (AKM) Arrangement Training for Senior High School Teacher Organization of Indonesian Language Subject in Bangkalan Region - Kayati, Afiyah Nur; Fiyan Ilman Faqih; Prita Dellia; Shofa Qolbiyatun N.L.; Nailul Izzah (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Literacy skills are needed to increase the minimum assessment competency (AKM) scores and the quality of education in educational units. To improve students' literacy competence, not only reading materials are needed but also literacy assessments. Hence, teachers need the competence to create literacy questions that are different from formative and summative assessment questions. This service aims to improve the ability of the senior high school teacher organization of Indonesian Language subject to prepare AKM literacy questions oriented towards local Madurese wisdom by utilizing digital applications. This community partnership service is carried out through five stages, including socialization, training, technology application, mentoring and evaluation, and program sustainability. The results of this training show that teachers are enthusiastic about taking part in the training which can be shown from the teacher responses, namely the clarity of the material is very good (96%), the ease of use of the guide is very good (95.1%), the understanding of literacy assessment is very good (95.5%), understanding of the forms of AKM questions is very good (96.8%), ability to compose AKM questions is very good (95.1%), ability to inventory Madurese local wisdom is very good (96%), ability to integrate Madurese local wisdom in literacy assessment is very good (96%), and the ability to utilize digital applications for preparing AKM literacy questions is very good (95.5%).